Women’s empowerment and the 2030 Agenda: an experience based in the process and outcomes from the Northeast of Brazil - Tavares, Celma (2021)
The empowerment of women constitutes one of the ways to reverse gender inequalities.  In this sense, analyzing experiences that articulate empowerment with human rights contributes to indicate their achievements and gaps and enable their expansion.  Thus, this text aims to discuss the women’s empowerment process articulated to the United Nations 2030 Agenda, taking as reference the experience developed with rural and urban women in Northeast Brazil by a feminist organization, in order to reduce the gender inequality relative to access, use and control of land, territory, decent housing and protection of nature.  The study, based on qualitative research and content analysis, focused on the evidence of the process based on the relationship between the lines of action and their respective results.  In general terms, it was observed that the work has been establishing the conditions to advance in the empowerment of women at the individual level; of the relationships within their movements of origin; and influence on public policies.  Thus, its replication in other territories is considered possible as long as its guidelines and methodology are maintained, and its development is adapted to local specificities.